Altruism, Self-Efficacy, Self-Actualization, and Their Effect on Employee Performance - Pratama, Salsa Wulandari; Sumarni, Nani; Hardjowikarto, Dharliana; Sulistiyowati, Lisa Harry (Research Collaboration Community (RCC), 2024)
The aim of this research was to investigate how altruism, self-efficacy, and self-actualization influence the performance of employees at BPR Kuningan Bank. This research uses a numerical technique and primary data collection through a Likert scale questionnaire distributed to employees of BPR Kuningan Bank through Google Form, the sample of this research was 85. Secondary data comes from official sources such as journals and books. This research is explanatory research that tests previously designed hypotheses or known as causality research and describes how research variables relate to one another. The outcomes indicated that self-efficacy favorablely and remarkablely influences employee performance, as evidenced by the t-value test outcomes. The computed t-value of 5,355 surpasses the critical t-value of 1,990, indicating a strong impact. Self-actualization demonstrates a favorable and remarkable influence on employee performance, as indicated by the statistical analysis of the t-value test, where the computed t-value of 4,209 exceeds the critical t-value of 1,990. However, altruism does not exhibit a favorable impact on employee performance, evidenced by the error rate (sig) of 0,136, which surpasses the threshold of 0,05. The combined effect of Altruism, Self-Efficacy, Self-Actualization on Employee Performance significance value in the anova table for the effect of X1, X2, X3 simultaneously / together on Y is 0,000 <0,05 and the value of F count 50,010> F table 2,716 so it can be concluded that H4 is accepted which means X1, X2, X3 have an effect on Y simultaneously.